2016
DOI: 10.5114/wo.2016.60065
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture: could it become everyday practice in oncology?

Abstract: Acupuncture is a complementary and alternative medical treatment (CAM) which is increasingly used in the care of cancer patients. Traditionally derived from Chinese medicine, nowadays it is becoming a part of evidence-based oncology. The use of acupuncture in these patients has been recommended by the American Cancer Society (ACS) for the treatment of side effects associated with conventional cancer therapy and cancer-related ailments. A growing body of evidence supports the use of acupuncture in the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
(10 reference statements)
0
8
0
Order By: Relevance
“…During this time the number of studies in cancer patients also increased 1, 2. There is a growing body of research on acupuncture in cancer care and cancer-related symptoms where many positive findings have emerged 2, 3, 4. The strength of evidence is not yet strong for symptoms other than CINV,10, 11 but it has increased so that authors now recognize that acupuncture may be effective for cancer pain,10, 11 aromatase inhibitor induced arthralgia (in breast cancer), fatigue, recovery after colorectal cancer resection 11 as well as symptoms also seen commonly in cancer patients such as post-operative nausea and vomiting (PONV), anxiety, depression and sleep problems 10, 11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this time the number of studies in cancer patients also increased 1, 2. There is a growing body of research on acupuncture in cancer care and cancer-related symptoms where many positive findings have emerged 2, 3, 4. The strength of evidence is not yet strong for symptoms other than CINV,10, 11 but it has increased so that authors now recognize that acupuncture may be effective for cancer pain,10, 11 aromatase inhibitor induced arthralgia (in breast cancer), fatigue, recovery after colorectal cancer resection 11 as well as symptoms also seen commonly in cancer patients such as post-operative nausea and vomiting (PONV), anxiety, depression and sleep problems 10, 11.…”
Section: Resultsmentioning
confidence: 99%
“…Acupuncture is increasingly used by patients with cancer to help treat symptoms of cancer, side effects of cancer therapies and in cancer survivors,1, 2 with a growing body of research and evidence in cancer care 2, 3, 4. This short narrative review summarizes evidence of effectiveness and safety of acupuncture for a range of symptoms in cancer patients and emergent evidence regarding how oncology specialists and oncology groups have digested that evidence and recommend acupuncture in patients with cancer and in cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…Male and female patients were included with 52.7% being female (267 out of 507). All patients had failed conservative therapies including escalating large doses of opioid, nonnarcotics, complementary and alternative medicines, acupuncture, mind-body medicine, and physical therapy (21,22). All the patients were in various stages of cancer and in progression states and had uncontrolled pain.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that yoga, intense physical exercise, meditation, acupuncture, dark chocolate consumption, singing, dancing improves the psychological status by reducing stress, increases social bonding by oxytocin release, physical status, increase immune cells and their activity such as macrophages, NK cells, T and B lymphocytes by beta endorphins release in patients with cancers, lead to lowering inflammation, cellular function enhancement, improves health outcome, later results in better prognosis [1,[16][17][18][19][20][21][22][23][24]27,29,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Clinical Studies Of Beta Endorphins On Different Types Of Camentioning
confidence: 99%